Function of Perceived Corporate Social Responsibility in Safety of Sports Activities and Home Aerobic Equipment in the Late Period of COVID-19 - Ma, Lang; Liu, Jiang; Liu, Yicheng; Zhang, Yue; Yang, Chunmei (Frontiers in Psychology, 2022)
The COVID-19 pandemic has impacted various industries, including the sports industry. However, corporate social responsibility can mitigate the adverse effects of the crisis and promote the sports industry. To analyze the effect of CSR, the study examined the impact of perceived corporate social responsibility on injury prevention expectation, injury risk perception, and health upgradation with the mediation of sports safety measure. 259 sportsmen of local sports bodies provided the data through a self-administered survey. Data analysis was conducted through Smart PLS and SEM techniques. The outcome of the analysis showed that perceived corporate social responsibility leads to injury prevention expectation, injury risk perception, and health upgradation. Also, the study found that sports safety measure mediates the relationship between perceived corporate social responsibility and injury prevention expectation, between perceived corporate social responsibility and injury risk perception, and between perceived corporate social responsibility and health upgradation among sportsmen of local sports bodies. The theoretical implications were presented that were related to the significance of CSR and sports safety measure and their impact on sportsmen injury prevention expectation, health, and risk perception. The practical implications were related to the management of local sports bodies and how they can induce CSR initiatives and programs. Some limitations related to sample size, incorporating other variables, examining the model in other contexts, and using differ study designs have also been mentioned in the study.